2019
DOI: 10.1186/s12866-019-1501-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of fungal communities during Gastrodia elata growth

Abstract: Background Gastrodia elata is a widely distributed achlorophyllous orchid and is highly valued as both medicine and food. Gastrodia elata produces dust-like seeds and relies on mycorrhizal fungi for its germination and growth. In its life cycle, G. elata is considered to switch from a specific single-fungus relationship ( Mycena ) to another single-fungus relationship ( Armillaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 60 publications
2
40
0
Order By: Relevance
“…The litter-decaying fungus, Mycena , induces seed germination, whereas the wood-decaying Armillaria supports further development of the mature plant (Xu and Guo 2000 ). A recent high-throughput sequencing study suggests that more diverse fungal groups than previously assumed are involved at the juvenile stage of G. elata (Chen et al 2019 ). Partner switching also seems to occur in Cyrtosia septentrionalis , the adult stage of which is associated with Armillaria (e.g., Hamada 1939 ).…”
Section: Fungal Partner Shift During the Plant Life Cyclementioning
confidence: 99%
“…The litter-decaying fungus, Mycena , induces seed germination, whereas the wood-decaying Armillaria supports further development of the mature plant (Xu and Guo 2000 ). A recent high-throughput sequencing study suggests that more diverse fungal groups than previously assumed are involved at the juvenile stage of G. elata (Chen et al 2019 ). Partner switching also seems to occur in Cyrtosia septentrionalis , the adult stage of which is associated with Armillaria (e.g., Hamada 1939 ).…”
Section: Fungal Partner Shift During the Plant Life Cyclementioning
confidence: 99%
“…Ontogenetic shifts (intrinsic) are developmentally programmed changes in a plant's physiological needs independently of extrinsic changes, such as growth from juvenile to adult (Rasmussen et al ., 2015), or from vegetative to reproductive life stages. For example, a field study on the orchid Gastrodia elata showed different fungal operative taxonomic units (OTUs) between protocorms and tubers, a later developmental stage (Chen et al ., 2019). As the two developmental stages occurred simultaneously, temporal variation in extrinsic factors can be ruled out as a cause for the switch.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-throughput sequencing of both juvenile and adult stages ofG. elata showed that the juvenile stage associated with more diverse fungal groups than Mycena only (Chen et al, 2019). A similar pattern of total replacement has been found in Cyrtosia septentrionalis , another mycoheterotrophic orchid associated with wood-decaying fungi.…”
Section: The Shift Of Fungal Partner In Different Developmental Stagesmentioning
confidence: 53%
“…A similar result was found in Gastrodia elata , which is mainly found in broadleaved forests. Chen et al (2019) showed that besides Mycenaceae, a broader spectrum of fungal associations, such as Resinicium ,Hyphodontia , Sistotrema , Tricholoma andRussula was detected in the juvenile stage of G. elata .…”
Section: Mycorrhizal Communities Associating With Gastrodia Confusoidesmentioning
confidence: 99%